IOP Conference Series: Earth and Environmental Science - Ilyashchenko, D. P. specialist in the field of welding production Associate Professor of the Yurga Technological Institute (branch) of Tomsk Polytechnic University, Candidate of Technical Sciences 1980- (2018)
The paper presents results the research in the effect of power sources dynamic characteristics on stability of melting and electrode metal transfer to the weld pool shielded metal arc welding. It is proved that when applying inverter-type welding power sources, heat and mass transfer characteristics change, arc gap short-circuit time and drop generation time are reduced. This leads to reduction of weld pool heat content and contraction of the heat-affected zone by 36% in comparison the same parameters obtained using a diode rectifier.